2023
DOI: 10.1093/biomethods/bpad026
|View full text |Cite
|
Sign up to set email alerts
|

A method for measurement of human asparagine synthetase (ASNS) activity and application to ASNS protein variants associated with ASNS deficiency

Mario C Chang,
Stephen J Staklinski,
Matthew E Merritt
et al.

Abstract: Human asparagine synthetase (ASNS) catalyzes the conversion of aspartate to asparagine in an ATP-dependent reaction that utilizes glutamine as a nitrogen source while generating glutamate, AMP, and pyrophosphate as additional products. Asparagine Synthetase Deficiency (ASNSD) is an inborn error of metabolism in which children present with homozygous or compound heterozygous mutations in the ASNS gene. These mutations result in ASNS variant protein expression. It is believed that these variant ASNS proteins hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that the disordered C-terminal tail is functional and essential for synthetase activity in AsnB (Meyer, 2010), consistent with clinical observations of the ASNSD-linked C-terminal tail variants. Several ASNSD variants have been characterized using the purified protein and/or cell-based assays (Zhu et al, 2019;Matsumoto et al, 2021;Staklinski et al, 2022;Chang et al, 2023). In some cases, decreased stability and enzyme activity are attributed to ASNS dysfunction.…”
Section: Variantmentioning
confidence: 99%
“…Studies have shown that the disordered C-terminal tail is functional and essential for synthetase activity in AsnB (Meyer, 2010), consistent with clinical observations of the ASNSD-linked C-terminal tail variants. Several ASNSD variants have been characterized using the purified protein and/or cell-based assays (Zhu et al, 2019;Matsumoto et al, 2021;Staklinski et al, 2022;Chang et al, 2023). In some cases, decreased stability and enzyme activity are attributed to ASNS dysfunction.…”
Section: Variantmentioning
confidence: 99%